2012
DOI: 10.3233/jad-2012-120763
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ramipril in Individuals at Risk for Alzheimer's Disease: Results of a Pilot Clinical Trial

Abstract: Research shows that certain antihypertensives taken during midlife confer Alzheimer’s disease (AD) related benefits in later life. We conducted a clinical trial to evaluate the extent to which the angiotensin converting enzyme inhibitor (ACE-I), ramipril, affects AD biomarkers including CSF amyloid β levels (Aβ) and ACE activity, arterial function and cognition in participants with a parental history of AD. This four month randomized, double-blind, placebo-controlled, pilot clinical trial evaluated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 49 publications
2
49
1
Order By: Relevance
“…Some prior studies have suggested cognitive and functional benefits of BBB‐crossing RAS‐acting antihypertensive medications. Epidemiological, histopathological, and more recently, clinical data suggest that the RAS is involved in AD incidence and progression, potentially through direct actions on A β neuropathology . Another study assessed the ability of 55 different antihypertensives to reduce A β oligomerization in vitro in hippocampal neurons from Tg2576 AD mice and found that RAS‐acting medications (valsartan) attenuated oligomeric A β pathology and A β ‐mediated cognitive deterioration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some prior studies have suggested cognitive and functional benefits of BBB‐crossing RAS‐acting antihypertensive medications. Epidemiological, histopathological, and more recently, clinical data suggest that the RAS is involved in AD incidence and progression, potentially through direct actions on A β neuropathology . Another study assessed the ability of 55 different antihypertensives to reduce A β oligomerization in vitro in hippocampal neurons from Tg2576 AD mice and found that RAS‐acting medications (valsartan) attenuated oligomeric A β pathology and A β ‐mediated cognitive deterioration .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of BBB permeability to cognitive impairment, as well as the salutary influence of BBB‐crossing RAS‐acting medications on cognition, have been reported . Moreover, BBB‐crossing RAS‐acting medications significantly reduce ACE levels in the brain in individuals at risk for AD by virtue of parental history …”
Section: Discussionmentioning
confidence: 99%
“…Extended treatment and follow-up periods and larger sample sizes will likely be needed to reliably detect the effects of BP lowering on cognitive measures. By comparison, neurodegenerative and dementia-specific biomarkers (e.g., hippocampal atrophy and CSF-tau) may be more sensitive to treatment-related effects, but their validity as intermediate endpoints remains a subject of debate [181,182]. Future studies may also benefit from making use of a more comprehensive cognitive battery.…”
Section: Antihypertensive Clinical Trials To Improve Cognitionmentioning
confidence: 99%
“…67 Ramiprilat penetrates from the blood into the CSF which inhibits the activity of soluble ACE at the spinal cord region. 68,69 Therefore, neuropathic pain parameters have assessed on the peripheral site (paw pain sensitivity response) as well as in the central site (tail pain sensitivity response).…”
Section: Discussionmentioning
confidence: 99%